Kesiapan Bersekolah dalam Transisi dari PAUD ke Pendidikan Dasar: Perspektif Ekologis dan Multidimensional - Wulan Feronika Maharani; Putri Maratus Sholikhah; Taufika Nururrohmah; Mohamad Azhar Annawa UBM (Lembaga Pusat Kegiatan Belajar Masyarakat (PKBM) Tunas Harapan, 2026)
The transition from Early Childhood Education (ECE) to primary school is a critical developmental stage that influences children's academic and social success. This study aimed to synthesize the literature on school readiness during the transition from ECE to primary school from ecological and multidimensional perspectives. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Articles were retrieved from Google Scholar, Portal Garuda, DOAJ, and Semantic Scholar between January 2020 and May 2026. Of the 380 records identified, 41 studies met the inclusion criteria and were analyzed using thematic synthesis. The findings indicate that school readiness comprises six key dimensions: social-emotional development, cognitive development, language and literacy, self-regulation, physical-motor development, and approaches to learning. Among these, social-emotional development and self-regulation emerged as the most consistent predictors of successful school transition. School readiness is influenced by ecological factors across all levels of Bronfenbrenner's ecological systems. Effective transition practices include parent psychoeducation, play-based learning activities, and collaboration among key stakeholders, whereas an excessive emphasis on early literacy and numeracy instruction and weak alignment between ECE and primary education remain major barriers. The findings highlight the importance of holistic, collaborative, and ecologically informed assessment and transition programs to support children's successful transition to primary school.